"Hong Kong, Add Oil!": The Lennon Walls in the 2019 Hong Kong Movement. (February 2021) - Li, Yao-Tai; Liu, John Chung-En
In June 2019, millions poured onto the streets of Hong Kong to protest the proposed Extradition Bill. In addition to physical confrontations between the police and protesters on the streets, Lennon Walls were also erected. This essay captures the zeitgeist of the Hong Kong 2019 movement through post-it notes on Lennon Walls across Hong Kong's major districts.